Effects of Root Endophytic Fungi on Response of Chenopodium Quinoa to Drought Stress - Urzua-Moll, A; Gonzalez-Teuber, M (Springer Science and Business Media B.V., 2018)
Symbiotic associations with microbes can help plants to respond to environmental changes. In this study, we investigated how colonization by root endophytic fungi enhances performance of Chenopodium quinoa and its ability to cope with extended periods of drought. The fungus Penicillium minioluteum, which was isolated from quinoa naturally occurring in the Atacama Desert, was used for endophyte colonization. We developed a greenhouse experiment, subjecting endophyte-infected (E+) and endophyte-free (E−) plants to two treatments: water deficit and abundant water availability. Differences in plant performance, photosynthesis, water-use efficiency and photochemical efficiency between E+ and E− plants under both water treatments were examined. We assessed the nature of the plant–symbiont interaction (parasitic or mutualistic) under both treatment conditions. We found that P. minioluteum initially affected radicle growth, subsequently triggering improvements in root formation, with the latter particularly evident under drought conditions. Under low water, E+ plants demonstrated a 40% improvement in root formation relative to E− plants; however, physiological responses to drought were not demonstrably enhanced by the presence of endophytic fungi. The nature of the interaction appeared to be positive, but only under conditions of water stress. Our study demonstrates that, in C. quinoa, P. minioluteum assists in coping with water stress primarily by affecting substantial root biomass adjustments, and that host benefits in this relationship are conferred in conditions of stress only. © 2017, Springer Science+Business Media B.V., part of Springer Nature.